Phosphorus restrictions for land application of biosolids: Current status and future trends - Shober, A.L; Sims, J.T (Journal of environmental quality, 2003)
The application at biosolids (sewage sludge) to agricultural soils provides P in excess of crop needs when applied to meet the N needs of most agronomic crops. These overapplications can result in the buildup of P in soils to values well above those needed for optimum crop yields and also may increase risk of P losses to surface and ground waters. Because of concerns regarding the influence of P on water quality in the USA, many state and federal agencies now recommend or require P-based nutrient management plans for animal manures. Similar actions are now under consideration for the land application of biosolids. We reviewed the literature on this subject and conducted a national survey to determine if states had restrictions on P levels in biosolids-amended soils. The literature review indicates that while the current N-based approach to biosolids management does result in increases of soil P, some properties of biosolids may mitigate the environmental risk to water quality associated with land application of P in biosolids. Results of the survey showed that 24 states have regulations or guidelines that can be imposed to restrict land application of biosolids based on P. Many of these states use numerical thresholds for P in biosolids-amended soils that are based on soil test phosphorus (STP) values that are much greater than the values considered to be agronomically beneficial. We suggest there is the need for a comprehensive environmental risk assessment of biosolids P. If risk assessment suggests the need for regulation of biosolids application, we suggest regulations be based on the P Site Index (PSI), which is the method being used by most states for animal manure management.